Australasian Federal Convention, Melbourne, 1898 (1898)
Album of photographic portraits and signatures.
Cover title.
Cover inscribed to Sir Edmund Barton, Leader of the Convention.
Images individually catalogued and digitised.
Also available online
Keywords: Zeal, William Austin, -- Sir, -- 1830-1912.; Barton, Edmund, -- Sir, -- 1849-1920.; Australia. -- Constitutional Convention, -- (1898) -- Photographs; Politicians -- Australia -- Portraits